Perancangan Dan Implementasi Sistem Informasi Presensi Terpadu Pada Politeknik Negeri Padang - Roni Putra; Surfa Yondri; Ervan Asri; Revalin Herdianto; Junaldi (SOTVI - Society of Visual Informatics, 2020)
Making lecture schedules manually is very difficult. We have to check every schedule if it does not conflict with the existing schedule and is time consuming and inefficient because of frequent errors. After the schedule is complete, every day there is a process of student attendance recapitulation and lecturer attendance recapitulation, this process often occurs with recap errors and is very long, for example student recaps can be done for months and when informing student compliance is late, many students complain. With this problem, the authors make changes so that the problem is resolved by using the FET application for scheduling lectures quickly, efficiently and accurately, the results of the lecture schedule we can import into the MySQL database then will be displayed and processed in the form of an information system-based website. can manage student and lecturer attendance online recap quickly and accurately.